In the Valley of the King: Jerusalem's Rural Hinterland in the 8th-4th Centuries BCE. (June 2015) - Gadot, Yuval
Abstract : The author proposes that an unprecedented growth in the number of rural settlements around Jerusalem took place during the 7th century BCE and not, as has been broadly maintained, in the 8th century BCE. He also shows that the decrease in the number of sites in the transition to the Persian period is less dramatic than has previously been claimed. The author asserts that the large number of 7th century BCE sites around Jerusalem is the result of the devastation of the Shephelah wrought by Sennacherib and that a relatively large number of Iron Age sites survived into the Persian period due to the role played by Ramat Raḥel, which replaced Jerusalem as the economic and political hub of the southern highlands.